2009
DOI: 10.1016/j.cell.2008.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Importin 8 Is a Gene Silencing Factor that Targets Argonaute Proteins to Distinct mRNAs

Abstract: Small regulatory RNAs including small interfering RNAs (siRNAs) and microRNAs (miRNAs) guide Argonaute (Ago) proteins to specific target RNAs leading to mRNA destabilization or translational repression. Here, we report the identification of Importin 8 (Imp8) as a component of miRNA-guided regulatory pathways. We show that Imp8 interacts with Ago proteins and localizes to cytoplasmic processing bodies (P bodies), structures involved in RNA metabolism. Furthermore, we detect Ago2 in the nucleus of HeLa cells, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
274
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(300 citation statements)
references
References 53 publications
17
274
0
1
Order By: Relevance
“…2C), implying that the import of Ago2 into the nucleus is IPO8-dependent. Reduction of the nuclear Ago2 pool by IPO8 knockdown has also been demonstrated recently by Weinmann et al (16). The involvement of the Ago2 complex in IPO8-mediated cytoplasm-to-nucleus transport of miRNAs is further supported by the observation that TPF, a small molecule that specifically disrupts the association of Ago2 with miRNAs (14,17), blocked the cytoplasm-to-nuclear transport of all six nuclear miRNAs.…”
Section: Resultssupporting
confidence: 63%
“…2C), implying that the import of Ago2 into the nucleus is IPO8-dependent. Reduction of the nuclear Ago2 pool by IPO8 knockdown has also been demonstrated recently by Weinmann et al (16). The involvement of the Ago2 complex in IPO8-mediated cytoplasm-to-nucleus transport of miRNAs is further supported by the observation that TPF, a small molecule that specifically disrupts the association of Ago2 with miRNAs (14,17), blocked the cytoplasm-to-nuclear transport of all six nuclear miRNAs.…”
Section: Resultssupporting
confidence: 63%
“…5). Consistent with this observation, MALAT1 has previously been shown to be associated with Ago2 (also known as EIF2C2), a known component of the sRNA processing machinery (Weinmann et al 2009). This analysis indicates that the large majority of our lncRNAs are not processed into sRNAs.…”
Section: Genomic Characterization Of Embryonic Lncrnassupporting
confidence: 60%
“…Robb et al fi rst showed the presence of active Argonaute proteins in nuclear compartments (Robb et al, 2005). In addition, Weinmann et al detected AGO2 in the nucleus of HeLa cells (Weinmann et al, 2009). Notably, it has been shown that Argonaute proteins are directly associated with nuclear miRNAs in Caenorhabditis elegans (C. elegans) (Zisoulis et al, 2012) and human cells (Hansen et al, 2011;Zisoulis et al, 2012).…”
Section: Protein Cell and Presence Of Argonaute Proteins In The Nucleusmentioning
confidence: 99%
“…These two papers suggest that Exportin-1 may serve as a pore for the translocation of both miRNAs and Argonaute proteins from the cytoplasm to the nucleus. In another interesting study, Weinmann et al showed that Importin-8 interacted with human Argonaute proteins in a Ran-dependent manner (Weinmann et al, 2009). Additionally, they found that upon Importin-8 knockdown, the localization of AGO2 was shifted from the nucleus to the cytoplasm, whereas the total amount of AGO2 remained unaffected (Weinmann et al, 2009).…”
Section: Mini-review Protein Cellmentioning
confidence: 99%
See 1 more Smart Citation